2018
DOI: 10.1080/17452759.2018.1548069
|View full text |Cite
|
Sign up to set email alerts
|

Ductility of 3D printed concrete reinforced with short straight steel fibers

Abstract: With the number of 3D printed concrete structures rapidly increasing, the demand for concepts that allow for robust and ductile printed objects becomes increasingly pressing. An obvious solution strategy is the inclusion of fibers in the printed material. In this study, the effect of adding short straight steel fibers on the failure behaviour of Weber 3D 115-1 print mortar has been studied through several CMOD tests on cast and printed concrete, on different scales. The experiments have also been simulated num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(55 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…In their work, the authors focused on the fiber/matrix interface, which is the main factor governing the mechanical behavior of the reinforced material. Bos et al [63] investigated the ductility of 3D-printed concrete reinforced with short straight steel fibers. They showed that the fibers improve the flexural strength of printed concrete bringing it to a value similar to the cast concrete.…”
Section: Methodsmentioning
confidence: 99%
“…In their work, the authors focused on the fiber/matrix interface, which is the main factor governing the mechanical behavior of the reinforced material. Bos et al [63] investigated the ductility of 3D-printed concrete reinforced with short straight steel fibers. They showed that the fibers improve the flexural strength of printed concrete bringing it to a value similar to the cast concrete.…”
Section: Methodsmentioning
confidence: 99%
“…The flexural tests were performed as 3-point bending tests according to NEN-EN 196-1, on the same bench, at a rate of 50 N/s (load-controlled). The CMOD tests were performed according to NEN-EN 14651 (NEN-EN 14651:2005EN 2005) but on scaled down specimens (Bos, Bosco, and Salet 2019) have extensively argued this is allowable. The loading rate was controlled by the crack mouth opening, at 0.05 mm/min until a CMOD of 0.1 mm is reached and at 0.2 mm/min until the end of the test (either specimen fracture or when a CMOD of 4.1 mm was reached).…”
Section: Methodsmentioning
confidence: 99%
“…Fibers made of different materials are available. However, steel fibers are used most frequently [12].…”
Section: Reinforcement Systems For Extrusion (State Of the Art)mentioning
confidence: 99%